Unveiling halophilic microbial communities in calcite fossil sedimentary rocks and their implications for biomineralization - Chinnappa, Balachandar; Thirupathi, Balaji; Sundaram, Thanigaivel; Pongen, Yimtar L.; Vinayagam, Saranya; Gnanasekaran, Lalitha; Rajput, Vishnu D.; Durairaj, Thirumurugan (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2025)
This study investigated the microbial diversity, crucial for pedogenesis, within limestone soil samples obtained from deep-earth layers to understand their role in bio-mineralization processes, formation of mineral deposits and evolutionary significance. A total of eighteen distinct bacterial isolates were isolated and four of them are moderately halophilic (growth sustainability up to 15 % NaCl) and were chosen as subjects for this study. Biofilm formation in addition to the positive results in urease and carbonic anhydrase assays confirmed the presence of biomineralizing Microbially Induced Calcite Precipitation (MICP) pathways in these potent isolates. Subsequent calcite precipitation experiments in B4 media yielded crystals, which were then subjected to FTIR and x-ray diffraction analysis, validated calcite precipitation. From the 16S rRNA-based phylogenetic analysis, these isolates were found to be the nearest relatives of marine origin organisms belonging to Halobacillus sp., Staphylococcus sp. and Enterobacter sp. Considerable differences in phylogenetic score and relevant molecular clock timeline analysis underlined the novelty in species level variation with contemporary bacterial 16S rRNA sequences in addition to archaic evolutionary identity with bacterial nodes diverged around 125 MYA during the Jurassic era. Upon considering their biomineralizing potential and correlative phylogenetic identity with marine-origin archaic bacterial communities, it is inferred that these subsurface dwelling communities which are being reported for the first time from Ariyalur Limestone fossils could have played a vital role in the genesis of the calcite fossil environment belonging to Jurassic era and may possess many commercial implications to be studied such as bio-cementation, saline tolerant bioactive molecules, etc. [Display omitted] •An investigation of moderately halophilic bacterial communities from the subsurface limestone fossil layers•Screening the metabolic pathways involved in microbially induced calcite precipitation•Phylogenetic analysis and their relevant timeline tree analysis revealed the archaic significance of the isolates•A potential application of bacteria is bio-cementation and concrete healing